Child’s heart development and contractility from prenatal to postnatal period - E. N. Pavlyukova; M. V. Kolosova; A. I. Unasheva; G. V. Neklyudova; R. S. Karpov (Российский кардиологический журнал)
This literature review analyzes current data on the main stages of child’s heart contractility development from prenatal to postnatal period. The presented information will expand the conventional ideas on the age-related cardiovascular physiology in children, supplementing with relevant knowledge about the patterns of left ventricular mechanics, and the mechanisms affecting child’s heart morphology. In addition, we consider the evolutionary feasibility of the simultaneous existence of various left ventricular mechanics models, which ensure the effective cardiac function in the postnatal period. This is very important for the work of neonatologists, pediatricians, pediatric cardiologists and therapists.